Balancing between paidia and ludus: video games in school's teaching and learning process - Ivanauskienė, Gintė Marija (Acta Paedagogica Vilnensia, 2022)
Play, even though usually regarded as a natural practice for children, is a multifaceted, hard to define phenomenon, which connects to distinct features: playfulness and seriousness. The pragmatist J. Dewey has noted many links between education and play. But with technology advancing every day and with play having acquired a new form – video games – the ways in which we can integrate play into the process of education is still in its experimental phase. Even though the popularity and potential of this medium is vast, video games are very rarely included in the process of formal education in Lithuania. This article aims to discuss the ambiguous (paidia and ludus) nature of video games: what challenges and possibilities this characteristic brings into teaching and learning in schools while integrating video games. The empirical part – a case study of the project „Big Small Screens. Media Literacy in Schools of Lithuania“ (analysis of the documents and the interviews with teachers, who selected video games while participated in the project), started by VšĮ „Meno avilys“ in 2016, which ,among other audiovisual medias, video games were analyzed. The research shows that the project tries to highlight the serious side (ludus) of video games, which is less familiar in schools, suggesting to integrate it in class when analyzing and creating (them or with them). Yet the experiences of the teachers revealed that they are more likely to use the playful side (paidia) of video games in their classes and experience difficulty when integrating the serious side of video games because of various challenges, thus the possibilities of integrating video games in teaching and learning is limited.
Keywords: seriousness; playfulness; video games; play; school; media literacy